Introducing communication research : paths of inquiry - Treadwell, Donald, ....- (Los Angeles : SAGE Publications, 2016)
Introducing Communication Research: Paths of Inquiry helps students understand the communication research process from start to finish.
Keywords: Communicatie -- Onderzoek